Orbital Lymphoma: Clinical Features and Management at Dr. M. Djamil General Hospital in 2018 - Messia Refri Rahmi; Ardizal Rahman (HM Publisher, 2022)
Background: Orbital lymphoma is found in 50-60% of ocular adnexal lymphomas, with approximately 90% of orbital lymphomas being Non-Hodgkin's lymphomas. Clinical features may include proptosis, ptosis, limitation of eye movement, and salmon patch lesions on the conjunctiva. If an orbital tumor is present, an accurate histopathological examination is important in the management of orbital lymphoma. Because of nonspecific clinical signs and symptoms, some diagnostic delays may occur. The purpose of the study was to evaluate the clinical features, diagnostic approach, and treatment choice in orbital lymphomas. Methods: We identified patients diagnosed with orbital lymphoma in an outpatient clinic in Dr. M. Djamil General Hospital from January to December 2018. Patients’ medical records were reviewed retrospectively. Results: The patient group consisted of 6 patients (five males and one female) with a median age of 58 years. Proptosis and orbital swelling were the leading clinical symptoms, mainly found unilateral (five cases). The diagnosis was confirmed by a surgical biopsy. One histology result showed lymph node hyperplasia, which didn't suit the clinical manifestation and got re-reviewed. All histology results then showed non-Hodgkin’s lymphoma with the small lymphocytic type (100%). Five patients received systemic chemotherapy with the CHOP regimen protocol, and one patient refused to get further chemotherapy treatment. Conclusion: When unmatched orbital symptoms with histology results are present, re-reviewing the histology result is essential. Once the diagnosis is established, systemic chemotherapy is indicated and can proceed so there will be no delay in treatment